Antioxidant Compound, Oxyresveratrol, Inhibits APP Production through the AMPK/ULK1/mTOR-Mediated Autophagy Pathway in Mouse Cortical Astrocytes - Md. Ataur Rahman; Yoonjeong Cho; Ghilsoo Nam; Hyewhon Rhim (MDPI AG, 2021)
Oxyresveratrol (OxyR), a well-known polyphenolic phytoalexin, possesses a wide range of pharmacological and biological properties, comprising antioxidant, anti-inflammatory, free radical scavenging, anti-cancer, and neuroprotective activities. Autophagy is a cellular self-degradation system that removes aggregated or misfolded intracellular components via the autophagosome-lysosomal pathway. Astrocyte accumulation is one of the earliest neuropathological changes in Alzheimer's disease (AD), and amyloid precursor protein (APP) is the hallmark of AD. OxyR could affect APP modulation via the autophagy pathway. Here, we have reported that OxyR promotes autophagy signaling and attenuates APP production in primary cortical astrocytes based on immunofluorescence and immunoblotting assay results. Co-treatment with the late-stage autophagy inhibitor chloroquine (CQ) and OxyR caused significantly higher microtubule-associated protein light chain 3 (LC3)-II protein levels and LC3 puncta counts, demonstrating that OxyR stimulated autophagic flux. We also found that OxyR significantly reduced the levels of the autophagy substrate p62/SQSTM1, and p62 levels were significantly augmented by co-treatment with OxyR and CQ, because of the impaired deficiency of p62 in autolysosome. Likewise, pretreatment with the autophagy inhibitor, 3-methyladenine (3-MA), resulted in significantly fewer OxyR-induced LC3 puncta and lower LC3-II expression, suggesting that OxyR-mediated autophagy was dependent on the class III PI3-kinase pathway. In contrast, OxyR caused significantly lower LC3-II protein expression when pretreated with compound C, an AMP-activated protein kinase (AMPK) inhibitor, indicating that AMPK signaling regulated the OxyR-induced autophagic pathway. Additionally, co-treatment with OxyR with rapamycin intended to inhibit the mammalian target of rapamycin (mTOR) caused significantly lower levels of phospho-S6 ribosomal protein (pS6) and higher LC3-II expression, implying that OxyR-mediated autophagy was dependent on the mTOR pathway. Conversely, OxyR treatment significantly upregulated unc-51-like autophagy activating kinase 1 (ULK1) expression, and ULK1 small interfering RNAs (siRNA) caused significantly lower OxyR-induced LC3 puncta counts and LC3-II expression, indicating that ULK1 was essential for initiating OxyR-induced autophagy. However, we found that OxyR treatment astrocytes significantly increased the expression of lysosome-associated membrane protein 1 (LAMP1). Finally, we established a stress-induced APP production model using corticosterone (CORT) in cortical astrocytes, which produced significantly more APP than the equivalent using dexamethasone (DEX). In our experiment we found that CORT-induced APP production was significantly attenuated by OxyR through the autophagy pathway. Therefore, our study reveals that OxyR regulates AMPK/ULK1/mTOR-dependent autophagy induction and APP reduction in mouse cortical astrocytes.